The Impact of Performance Management on Employee Productivity At Al Ain Zoo, UAE (Global Journal of Management and Business Research, 2021)
This study aims at testing the relation between performance management and employee productivity at Al Ain Zoo, UAE. It also tests whether an organization such as a zoo uses the tradition appraisal approach or not, especially in the post-pandemic era. The management of Al Ain zoo forms the primary target audience for this study. It is a qualitative research that is exploratory in nature. The study is based on a primary approach of a 15-question interview. Data was collected from 3 employees of Al Ain Zoo, each operating at a different level of organizational hierarchy. Both hypotheses of the research were found to be true. A strong positive relationship exists between performance management and employee productivity. It is mainly attributable to the zoo's use of a modern performance management system called PABLO. The research recommends a use of a more decentralized management approach to further enhance employee satisfaction and productivity at Al Ain Zoo.
Keywords: performance management; employee productivity; al ain zoo; performance appraisal; HRM